Perubahan Musik Calung Punklung Menuju Musik Modern (Parakan Muncang-Kabupaten Sumedang Tahun 2003-2010) - Riyanti Nurina Fadillah; Widiati Isana (UIN Sunan Gunung Djati Bandung, 2020)
Calung art is one of the original arts typical of the West Java region and has existed since ancient times, and is commonly used during traditional ceremonies such as traditional ceremonies offered to Dewi Sri or better known as traditional ceremonies